The parallel tiled WZ factorization algorithm for multicore architectures - Bylina, Beata; Bylina, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this paper is to investigate dense linear algebra algorithms on shared memory multicore architectures. The design and implementation of a parallel tiled WZ factorization algorithm which can fully exploit such architectures are presented. Three parallel implementations of the algorithm are studied. The first one relies only on exploiting multithreaded BLAS (basic linear algebra subprograms) operations. The second implementation, except for BLAS operations, employs the OpenMP standard to use the loop-level parallelism. The third implementation, except for BLAS operations, employs the OpenMP task directive with the depend clause.
Keywords: tiled algorithm; WZ factorization; solution of linear systems; Amdahl`s law; high performance computing; multicore architectures